Squash Vine Borer Melittia cucurbitae (Harris) (Insecta: Lepidoptera: Sesiidae) - Eutychus Kariuki; Jennifer L. Gillett-Kaufman (EDIS, 2015)
Squash vine borer is a moth species that is active during the day (diurnal). The larvae complete their growth and development on wild and domesticated species of the genus Cucurbita. Once only considered a nuisance to commercial growers, with the expansion of cucurbit production in the United States over the last decade, the squash vine borer has become a pest of economic importance. This 5-page fact sheet was written by Eutychus Kariuki and Jennifer L. Gillett-Kaufman, and published by the UF Department of Entomology and Nematology, December 2014. (Photo: Lyle J. Buss, UF/IFAS)